(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Upper gastrointestinal endoscopy (UGE) allows physicians to directly schedule endoscopic procedures for their patients without prior consultation. Evaluation of appropriateness of endoscopic procedures is associated with costs and beneﬁts. Objectives: To assess the appropriateness of the use of UGE in an open-access setting in Bangladesh. Materials and Methods: This cross-sectional multicenter study was conducted among 300 patients referred for UGE at Dhaka Medical College Hospital and Shaheed Suhrawardi Medical College and Hospital from January 2016 to June 2016. The American Society for Gastrointestinal Endoscopy (ASGE) guidelines was used to assess the appropriateness of referral. The participants were selected by purposive nonprobability sampling and a pre-tested questionnaire was used for data collection. Results: Out of 300 respondents 62.3% was male. History of smoking was more in male and taking NSAIDs were more in the female. In UGE 46.7% revealed normal findings but majority 53.3% had some pathology. About 86% cases, UGE was found appropriate according to ASGE guideline and majority appropriate cases 37.3% were referred by internal medicine specialist. Appropriateness of referral among different physicians was not statistically significant. Conclusion: Appropriateness of referral for UGE performed in tertiary care level hospitals in an open-access setting like Bangladesh was satisfactory. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 152-155